The Use of Angklung As The Traditional Music Instrument to Stimulate The Artistic Skill of Preschoolers - Alim, Rahmawati Nur; Sri Rahayu (Institut Agama Islam Negeri Madura, 2024)
Music as an expression of the way children express their feelings through singing a song with loud and soft dynamics. The use of musical instruments such as angklung has become part of learning musical arts in most kindergarten due to the important of music that plays an essential role in a child's development particularly in art. This study aims to figure out the use of Angklung to increase the artistic skill of preschoolers in TK Kanisius Demangan Baru. The present study used qualitative method with descriptive approach. All data were collected from observations, documentations, and interviews with teachers and the school principal. Research findings indicate that playing angklung has a very good impact in improving children artistic. It was found that there are several artistic abilities that develop when learning angklung; being able to play the music instrument with good sound quality, suitability with the tempo, song pitch adjustment, mastery of the song rhythm, and being able to differentiate between good and bad musical tones. On top of that, the role of Angklung can enhance the sense of music to early childhood education.